Diferensiasi Karya Manual dan Digital - Mr. Wibowo (Ars: Jurnal Seni Rupa dan Desain, 2011)
The Differentiation between Manual and Digital Artwork. Technology always develops as time goes by. It reaches and covers wider geographic area from urban until sub-urban region. New technology transforms the skills mastered by designers. The manual age has been replaced by the digital age. The transformation is speeded up by the design software and hardware that support each other more in all stages: pre-production, production, and post-production/ finishing stage. Unfortunately, instead of  the fact that the technology development eases the work of  designers, just at this moment design world is marked by the production of  graphic designs with poor quality. One of  the reasons is that in this field, both the designer and the design devotees feel to have the right to determine the final result of  the designing process. It can be said that the advance technology and design equipment do not match with the designers’ conceptual ability. However, some designers still consider that manual skillis significant to create high-quality design.Keyword: manual, digital, technology